Top-gate transistors fabricated on epitaxially grown molybdenum disulfide and graphene hetero-structures. (12th November 2021) - Tsai, Po-Cheng; Huang, Hon-Chin; Chiang, Chen-Tu; Wu, Chao-Hsin; Lin, Shih-Yen
Abstract: We have demonstrated that by using the thermal evaporator, wafer-scale and uniform bi-layer MoS2 can be grown on graphene surfaces without introducing significant damage to the graphene channel. Compared with the top-gate transistors fabricated on standalone graphene films, the field-effect mobility value enhancement from 9.3 to 35.0 cm 2 V −1 ·s −1 is observed for the device fabricated on the MoS2 /graphene hetero-structures, which suggests that the MoS2 layer can act as an efficient passivation layer to the graphene channel. Similar field-effect mobility values obtained for the device with only a mono-layer MoS2 passivation layer are also demonstrated.